Plane symmetric vacuum bianchi type I cosmological model in Brans-Dicke theory - Ram S. (My University, 2025)
The paper presents an exact solution of the vacuum Brans-Dicke field equations for the metric tensor of a spatially homogeneous and anisotropic cosmological model. The Kasner metric is shown as a special case. Some physical properties of the model are discussed. © 1983 D. Reidel Publishing Co.